Effects of Exclusive Breast Feeding for First Six Months of life on Children Weight, Height and Head Circumference in Sulaimani City, Kurdistan-Iraq and Compare with Other Types of Feeding - Sardar M. Weli (College of Pharmacy University of Baghdad, 2021)
Breastfeeding (BF) serves as a complete nutritional source for the first six months of infant's life. Breast milk contains all essential nutrients that necessary for the physiological growth and development of infants. The aim of this study was to compare the physiological growth of infants including weight, height and head circumference who were exclusively breastfed for 6 months and those who were given bottle-fed or mixed fed and to find a percentage of exclusive breastfeeding among mothers who contributed in this study in Sulaimani city. This study was carried out in Sulaimani city/ Kurdistan region of Iraq and the cases were enrolled between the first of October 2018 and first of October 2019. The infants' weight, height and head circumstances were measured at different age levels (At age two, six, nine and fifteen months). The results of this study found that Among 198 mothers who were contributed in this study; 92 (46.5%) of mothers had EBF while 90 (45.5%) had mixed feeding and only 16 (8%) had exclusive formula feeding (EFF) in the first six months of baby's life. Infant's weight at age 2 months were no differences between types of feeding. However, at ages 6 and 9 were significantly high in infants who breastfed compared to formula fed but no differences were found between EBF and mixed feeding. At age 15 months weights of infants were again no differences were found between all types of feeding. For height parameter, infants who exclusively breastfed for six months were significantly higher than those of formula fed at age 2, 6, 9 and 15 months. Regarding head circumferences no significant differences between types of feeding at age 2 months were showed. Nevertheless, at age 6 and 15 months were significantly high in infants who breastfed than formula fed. The present study conclude that infants who breast fed for first six months of life have a higher weight, height and head circumferences than infants who exclusively formula fed. The percentage of EBF among Kurdish mothers were similar with other countries of Iraq but was low compared to the recommended rate of WHO.